Rancang Bangun Alat Pengukur Tinggi dan Berat Badan Secara Wireless Untuk Menentukan Status Gizi - Nadif Adhi Wibowo; Imam Tri Harsoyo; Pramesti Kusumaningtyas; Christina Ary Yuniarti; Muhammad Rofii (Unversitas Muhammadiyah Mataram, 2025)
Nutritional status is a key indicator in assessing individual health that can be determined through anthropometric measurements, particularly height and weight. This study uses a design approach that aims to design and implement a wireless system for measuring nutritional status based on Body Mass Index (BMI) using a TOF400C sensor and a Load Cell controlled by an ESP32 microcontroller. The TOF400C sensor measures height based on the Time-of-Flight principle of infrared light, while the Load Cell measures weight with the HX711 module. Data from both sensors is processed by the ESP32 to calculate BMI and categorize nutritional status according to WHO standards. Test results on 10 adult subjects showed an accuracy of 99.6% for the height measuring device and 98.3% for the weight measuring device compared to standard devices, as well as real-time results displayed on OLED and TFT screens. This system is expected to be a practical and efficient solution for digital nutritional status monitoring.